Enzymatic hydrophobization of jute fabrics and its effect on the mechanical and interfacial properties of jute/PP composites - Dong, A. (2016)
In this work, a hydrophobic surface of lignocellulosic jute fabric was achieved via the laccase-mediated grafting of octadecylamine (OA) on lignin moieties of jute aiming to improve the interfacial compatibility with the hydrophobic polypropylene (PP) resins in the fiber-reinforced composites. Firstly, the surface and total elemental compositions of the modified jute fabrics were investigated by X-ray photoelectron spectroscopy (XPS) and elemental analysis, respectively. The increases in the surface C/O ratio and total nitrogen content of jute fabrics after the laccase/OA treatment indicated that OA molecules were successfully grafted onto the jute surface mediated by laccase. The grafting percentage of OA on jute fabrics was 0.96%. The surface hydrophobicity of jute fabrics with static contact angle of 112.5°, advancing angle of 116.4° and receding angle of 42.7° supported the presence of nonpolar alkyl chains on the jute surface after the laccase-mediated OA-grafting. The tensile strength, tensile modulus as well as the elongation at break of the hydrophobized jute/PP composites were increased. The fracture surface of the composites became neat and the jute fibers on the section surface were surrounded by PP resins closely, which suggested better interfacial adhesion between the jute reinforcement and the PP resin.